OsWUS promotes tiller bud growth by establishing weak apical dominance in rice. (20th November 2020) - Xia, Tianyu; Chen, Hongqi; Dong, Sujun; Ma, Zeyang; Ren, Haibo; Zhu, Xudong; Fang, Xiaohua; Chen, Fan
Summary: Two branching strategies are exhibited in crops: enhanced apical dominance, as in maize; or weak apical dominance, as in rice. However, the underlying mechanism of weak apical dominance remains elusive. OsWUS, an ortholog of Arabidopsis WUSCHEL ( WUS ) in rice, is required for tiller development. In this study, we identified and functionally characterized a low‐tillering mutant decreased culm number 1 ( dc1 ) that resulted from loss‐of‐function of OsWUS . The dc1 tiller buds are viable but repressed by the main culm apex, leading to stronger apical dominance than that of the wild‐type (WT). Auxin response is enhanced in the dc1 mutant, and knocking out the auxin action‐associated gene ABERRANT SPIKELET AND PANICLE 1 ( ASP1 ) de‐repressed growth of the tiller buds in the dc1 mutant, suggesting that OsWUS and ASP1 are both involved in outgrowth of the rice tiller bud. Decapitation triggers higher contents of cytokinins in the shoot base of the dc1 mutant compared with those in the WT, and exogenous application of cytokinin is not sufficient for sustained growth of the dc1 tiller bud. Transcriptome analysis indicated that expression levels of transcription factors putatively bound by ORYZA SATIVA HOMEOBOX 1 (OSH1) are changed in response to decapitation and display a greater fold change in the dc1 mutant than that in the WT. Collectively, these findings reveal an important role of OsWUS in tiller bud growth by influencing apical dominance, and provide the basis for an improved understanding of tiller bud development in rice. Significance Statement: Cereal crops such as rice have multiple basal tillers, which exhibits a weak dominance of the apical meristem. We show here that loss of OsWUS function results in enhanced apical dominance, while decapitation or disruption of the auxin action‐associated gene ASP1 can release the inhibition of tiller bud by the apical meristem, suggesting that OsWUS plays important roles in establishing weak apical dominance in rice.